Experimental Investigation on Static Performance of Novel Precast Concrete Composite Slab–Composite Shear Wall Connections - Xiaozhen Shang; Ming Zheng; Yutao Guo; Liangdong Zhuang; Huqing Liang (Buildings)
The connection zones between precast concrete composite slabs and composite walls commonly experience severe reinforcement conflicts due to protruding rebars, significantly reducing construction efficiency. To address this, a novel slotted concrete composite slab–composite shear wall (SCS-CW) connection without protruding rebars is proposed in this study. In this novel connection, rectangular slots are introduced at the ends of the precast slabs, and lap-spliced reinforcement is placed within the slots to enable force transfer across the joint region. To investigate the static performance of SCS-CW connections, four groups of connection specimens were designed and fabricated. Using the structural detailing of the connection zone as the variable parameter, the mechanical performance of each specimen group was analyzed. The results show that the specimens demonstrated bending failure behavior. The key failure modes were yielding of the longitudinal reinforcement in the post-cast layer, yielding of the lap-spliced reinforcement, and concrete crushing at the precast slab ends within the plastic hinge zone. Compared to composite slab–composite wall connections with protruding rebars, the SCS-CW connections demonstrated superior ductility and a higher load-carrying capacity, satisfying the design requirements. Additionally, it was revealed that the anchorage length of lap-spliced reinforcement significantly affected the ultimate load-carrying capacity and ductility of SCS-CW connections, thus highlighting anchorage length as a critical design parameter for these connections. This study also presents methods for calculating the flexural bearing capacity and flexural stiffness of SCS-CW connections. Finally, finite element modeling was conducted on the connections to further investigate the influences of the lap-spliced reinforcement quantity, diameter, and anchorage length on the mechanical performance of the connections, and corresponding design recommendations are provided.